PRELIMINARY STUDY OF ROCK GEOCHEMISTRY FOR GOLD MINERALIZATION IN AREA-“X”, CENTRAL KALIMANTAN - Sunarie, Cecep Yandri; Fachrudin, Kurnia Arfiansyah; Barkah, M. Nursiyam; Hadian, M Sapari D.; Suganda, Bombom Rachmat; Helmi, Faisal (Journal of Geological Sciences and Applied Geology, 2021)
Area-“X” is located in the Central Kalimantan Province of Indonesia, one of several places in the Central Kalimantan region with a high potential for gold deposits. During the investigation, selected mineralized rock samples were collected, resulting in two rock outcrop samples and four rock float samples. All samples were analyzed for Au content at the local laboratorium using the Aqua Regia AAS method.  The lithology of the investigation area can be classified into two different rock units: The sedimentary rock unit and the igneous rock unit. The rock outcrop samples assay return with gold (Au) content from 0.21 ppm to 1.43 ppm. At the same time, the rock floated Au content from 0.79 ppm, Au, to 3.86 ppm. One rock outcrop sample named “Outcrop-001” identified as Quartz Vein up to 40cm width with N500E/850 strike and dip. The other two rock outcrop samples designated “Outcrop-002” and “Outcrop-003” are the parallel quartz veinlet up to 8cm width with strike N350E and unidentified dip. Based on field observation and assay results, this area-“X” has potential for gold mineralization as vein type.